Análisis jurídico y doctrinario de la figura de tentativa en el Código Orgánico Integral Penal - Ludeña Salinas, Diego Josué (2024)
The phenomenon of attempt has been complicated when establishing the doctrinal and legal parameters, since throughout the history of humanity, Roman law until today, has had a doctrinal variation that establishes different criteria for punitive assessment, but its recognition as an autonomous structure within the criminal sciences it is not very old, since it comes from classical criminal law. The attempt makes the configuration of the unjust impossible due to the lack of a typical result that is not executed due to conduct foreign to the agent, that is to say, this figure takes place when the author sets in motion in the real world the means chosen to achieve the proposed end. , which, however, was not consummated for reasons beyond its typical will. In the universal theory of iter criminis, the figure of the attempt is located after the preparatory acts, but before the consummation of the crime, being in many cases very difficult to differentiate it from the figure that precedes it. Therefore, there are several theories that allow us to establish a set of assumptions for the correct structuring of the attempt and separate it from the preparatory acts. Many considerations and theories surround the attempt to try to understand through the iter criminis, and justify its punishment, which is why it is considered by the law as a crime that must be punished depending on what doctrinal position it adopts. In our country, the attempt is established in a very general way, without any dogmatic construction, giving rise to a series of arbitrariness and erroneous application of this figure of the theory of crime, which makes clear the need to establish prior requirements or criteria that must be be seen by the members of the Courts, despite the fact that the law and doctrine are quite clear in this regard.